Burnout Syndrome among Healthcare Providers during Covid-19 Pandemic in Rural Tamil Nadu, South India: A Cross-Sectional Study - Vasantha Mallika M. C; Pretty Venis; Glannie A R; Liji Anna Varghese (Indian Association of Preventive and Social Medicine, 2022)
Introduction: The 2019 Coronavirus disease (COVID-19) pandemic has been a serious global threat with numerous researchesindicatingthat frontline healthcare personnelinvolved in its management and diagnosis are at risk of experiencing psychologicaldisturbances and deteriorating mental health. By definition, "burnout is a syndrome conceptualized as resulting from chronic workplace stress that has not been successfully managed". Burnout has been associated with increased mortality and morbidity. Objective: To estimate the prevalence of burnout syndrome and to determine the associated factors among healthcare providers in rural Tamilnadu during the COVID-19 pandemic.Method: A cross-sectional study was done among 120 healthcare providers from SreeMookambika Institute of Medical Sciences, Tamil Nadu during July 2021. Participants selected by convenient sampling technique were given pre-tested Maslach Burnout Inventory- Human Services Survey (MBI-HSS) questionnaire. Data were entered in MS Excel 2019 and analysis was done in SPSS v26.0. Descriptive statistics and Chi-square tests were applied.Results: Mean age of the participantswas 25.48±4.66 years.Among them, 46(38.3%) reported emotional exhaustion, 42(35%) depersonalization and 87(72.5%) reported a lower sense of personal accomplishment. The years of professional experience and the number of working hours per day were associated with emotional exhaustion and depersonalization (p<0.05). The different professional categories showed a significant association with Emotional Exhaustion (χ2=20.888,df=6, p=0.002) and Depersonalization(χ2=23.055,df=6. p=0.001) with high Burnout among doctors and nurses. Conclusion: This study highlights the importance of addressing burnout among healthcare personnel. The issues should be prioritized by authorities to develop appropriate interventions.